2020
DOI: 10.3390/pr8121668
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of MSWI Fly Ash in Switzerland: Heavy Metal Recovery Potential and Their Properties for Acid Leaching

Abstract: From the year 2021 on, heavy metals from Swiss municipal solid waste incineration (MSWI) fly ash (FA) must be recovered before landfilling. This is predominantly performed by acid leaching. As a basis for the development of defined recovery rates and for the implementation of the recovery process, the authorities and plant operators need information on the geochemical properties of FA. This study provides extended chemical and mineralogical characterization of all FA produced in 29 MSWI plants in Switzerland. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Table 1 summarizes the mean value of the FA composition over the entire project duration and indicates the standard deviation for each element concentration. Compared to the average heavy metal concentrations of Swiss fly ash [2], the FA treated at MSWI plant Linth shows elevated Zn (52,593 mg/kg), Pb (9378 mg/kg), Cu (2671 mg/kg) and Cd (332 mg/kg) concentrations.…”
Section: Fluwa Process At Mswi Plant Linth: Process Conditions and Comentioning
confidence: 82%
See 2 more Smart Citations
“…Table 1 summarizes the mean value of the FA composition over the entire project duration and indicates the standard deviation for each element concentration. Compared to the average heavy metal concentrations of Swiss fly ash [2], the FA treated at MSWI plant Linth shows elevated Zn (52,593 mg/kg), Pb (9378 mg/kg), Cu (2671 mg/kg) and Cd (332 mg/kg) concentrations.…”
Section: Fluwa Process At Mswi Plant Linth: Process Conditions and Comentioning
confidence: 82%
“…The time-resolved monitoring of the process conditions in reactor 3 have shown that in a continuous process, the L/S-ratio significantly influences process stability (Figure 3). This is by enhancing or diminishing the effects of naturally occurring fluctuations in both FA and acid scrub water compositions [2]. The FA as well as the scrub water composition depend strongly on the waste input as well as the type and condition of the flue gas cleaning system or dust removal system.…”
Section: Process Stability and Leaching Behaviour Of Zn Cu Pb CDmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SiNPs were also synthesized by chemical method. The purity of the synthesized silica nanoparticles [90] was 88%-96% [91]. The synthesized iron oxide nanoparticles were mainly magnetite, maghemite, and hematite by chemical approaches whose purity was 85%-92% [92].…”
Section: Cfa In Metallurgymentioning
confidence: 99%
“…Therefore, Ekanthalu et al [15] applied hydrothermal carbonization (HTC) to produce energy-rich hydrochar products and to enable phosphorous recovery. Based on an inventory of MSW incineration fly ash in Switzerland by Zucha et al [16], Weibel et al [17] studied metal recovery from these materials by acid leaching, whereas Wolffers et al [18] investigated co-leaching of MSW incineration fly ash and waste wood fly ash. These leaching processes yield aqueous solutions which are used by Hettenkofer et al [19] for copper recovery using polymer-assisted ultrafiltration.…”
mentioning
confidence: 99%